Recreational and conservative valuation of Bien Ho landscape - Tuan, Nguyen Thanh; Chi, Tran Thuy; Y, Tran Van; Mung, Vu Thi (Vietnam Journal of Earth Sciences, 2019)
Bien Ho is one of the volcanic landscapes showing lava eruptions that occurred millions of years ago. It is a symbol of the volcanic landscapes in the Tay Nguyen, Vietnam, which keeps a lot of values. This article aimed to quantify recreational and conservative values. The travel cost and contingent valuation method were used to estimate the recreational and conservative value (existence, bequest, and option value) of Bien Ho, respectively. The results indicated that the recreational and conservative value of Bien Ho volcanic landscape was 1,436.9 billion VND and 38.6 billion VND, respectively. The average willingness to pay in the contingent valuation method was 39,388 VND and depended only on ethnicity and age. The study used different populations to define survey samples according to each estimating method to improve the confident accuracy of the results.